2017
DOI: 10.1016/j.brainres.2017.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the N-terminal heterogeneity for the neuronal K-Cl cotransporter KCC2 function

Abstract: The neuron-specific K-Cl cotransporter KCC2 maintains the low intracellular chloride concentration required for the fast hyperpolarizing responses of the inhibitory neurotransmitters γ-aminobutyric acid (GABA) and glycine. The two KCC2 isoforms, KCC2a and KCC2b differ by their N-termini as a result of alternative promoter usage. Whereas the role of KCC2b in mediating the chloride transport is unequivocal, the physiological role of KCC2a in neurons has remained obscure. We show that KCC2a isoform can decrease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…One potent mechanism to rapidly and reversibly regulate the intrinsic transport rate and cell-surface abundance of KCC2 is phosphorylation and dephosphorylation of serine, threonine, and tyrosine residues (23). Recently, some progress in our understanding of the regulatory impact of specific phosphosites (27,34,35,39,41,43) and underlying kinases and phosphates (35)(36)(37)(43)(44)(45)(46) has been made.…”
Section: Discussionmentioning
confidence: 99%
“…One potent mechanism to rapidly and reversibly regulate the intrinsic transport rate and cell-surface abundance of KCC2 is phosphorylation and dephosphorylation of serine, threonine, and tyrosine residues (23). Recently, some progress in our understanding of the regulatory impact of specific phosphosites (27,34,35,39,41,43) and underlying kinases and phosphates (35)(36)(37)(43)(44)(45)(46) has been made.…”
Section: Discussionmentioning
confidence: 99%
“…ZT-1a inhibits NKCC1 but stimulates KCC3 activity. 86 Rb + flux assays have been utilized extensively as a reliable measurement of cation chloride cotransporter activity [51][52][53][54] . Therefore, the ability of ZT-1a to decrease inhibitory phosphorylation of KCC3 at Thr991/Thr1048 prompted us to assess ZT-1a's effect on KCC3 activity by measuring hypotonicity-stimulated 86 Rb + uptake in isotonic or hypotonic low Cl − conditions (Fig.…”
Section: Zt-1a Reduces Spak-dependent CCC Phosphorylation In Cellsmentioning
confidence: 99%
“…In vitro and in vivo analyses revealed that members of the with-no-lysine kinase (WNKs) family in combination with their downstream targets STE20/SPS1-related proline/alanine rich kinase (SPAK) and oxidative stress response kinase (OSR1) are the most prominent kinases that regulate KCC2 and NKCC1 activity in a reciprocal way. SPAK/OSR1, activated by WNK1, phosphorylate Thr 6 and Thr 1007 of KCC2 [48,59,[61][62][63][64]. WNKs also interact with a yet unknown kinase to phosphorylate Thr 906 of KCC2 [48,63].…”
Section: Introductionmentioning
confidence: 99%